1999
DOI: 10.1177/00912709922008137
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Adrenal Interactions of IL‐10 and Prednisone in Healthy Volunteers

Abstract: The pharmacokinetic and adrenal interactions of recombinant human interleukin-10 and prednisolone were examined in this open-label, randomized, four-way crossover study in 12 healthy adult male volunteers. Single doses of IL-10 (8 micrograms/kg s.c.), IL-10 with prednisone (15 mg p.o.), placebo with prednisone, or placebo were administered on four separate occasions with at least 3-week interceding washout periods. Measurements included plasma prednisone, prednisolone and cortisol, unbound prednisolone, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…17,19 In our study, the TBW-normalized mean free prednisolone oral clearance in male subjects was significantly higher than the corresponding mean in female subjects, regardless of race (by 22% in whites, 40% in blacks; p < 0.01, Table II). The TBW-normalized apparent volume of distribution was also higher in men than in women (by 32% in whites, 38% in blacks; p < 0.01).…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…17,19 In our study, the TBW-normalized mean free prednisolone oral clearance in male subjects was significantly higher than the corresponding mean in female subjects, regardless of race (by 22% in whites, 40% in blacks; p < 0.01, Table II). The TBW-normalized apparent volume of distribution was also higher in men than in women (by 32% in whites, 38% in blacks; p < 0.01).…”
Section: Discussionmentioning
confidence: 40%
“…Using previous data, 19 a sample size of 8 per group was calculated to provide a 90%power with an alpha level of 0.05 in detecting a 25 L/h (26% of the reported mean) difference in free prednisolone oral clearance with a standard deviation of 15 L/h. The study was approved by the Kaleida Health Millard Fillmore Hospital Institutional Review Board (Buffalo, NY).…”
Section: Methods Subjectsmentioning
confidence: 99%
“…9 In this study, we observed a significant increase in metabolism of prednisolone to prednisone due to LPS stimulation. An earlier study indicated the role of cytokines in suppressing the induction of cytochrome P-450 isoenymes, including CYP3A4, 22 which is partly responsible for the metabolism of prednisolone.…”
Section: Discussionmentioning
confidence: 49%
“…NO Generation through TNF-α- (7) (8) (9) where PreiNOS represents the precursor to inducible nitric oxide (iNOS) enzyme, k NO,# are intercompartmental rate constants describing the production of NO from TNF-α following LPS induction, the power coefficient (δ) adjusts for transduction, and k el,NO is the first-order elimination rate constant of NO x .…”
Section: No Dynamicsmentioning
confidence: 99%
“…Clinical trials in which IL-10 was administrated systemically to healthy volunteers have demonstrated that, at doses associated with biological activities, this cytokine has minimal side effects [209][210][211][212][213], including a mild flu-like syndrome [210], transient mild to moderate neutrophilia, monocytosis, lymphopenia (dramatic reductions of 40-70% in circulating lymphocytes expressing the T cell markers CD2, CD3, and CD7), and a delayed decrease of platelet count [209,210]. Thus, IL-10 has been proposed as a candidate for treatment of bacterial sepsis, and more generally as an effective anti-inflammatory agent [72] and clinical trials have shown that its systemic administration is followed by modest but significant improvement of psoriasis [214,215], Crohn's disease [216], rheumatoid arthritis [217], and chronic hepatitis C infection [218].…”
Section: Il-10 Administration: Possible Implications In the Preventiomentioning
confidence: 99%